Keterbatasan Jangkauan dan Mekanisme Perlindungan Korban oleh Lembaga Perlindungan Saksi dan Korban (LPSK) terhadap Korban Pemerkosaan di Indonesia - Mihot Lenardo; Najwa Aulia Ramadhani; Junifer Dame Panjaitan (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This research discusses the limited scope and mechanism of protection provided by the Witness and Victim Protection Agency (LPSK) for rape victims in Indonesia. The background of this research arises from the high rate of sexual violence and inequality in the provision of legal protection for victims, especially in the context of rape. The purpose of this research is to analyze the normative and practical obstacles faced by LPSK in providing effective protection, as well as evaluating whether the existing mechanisms have been responsive to the needs of victims. This research uses a normative juridical method with a statutory and case study approach. The research findings show that LPSK has limitations in authority, limited resources, and challenges in coordination between law enforcement agencies. In addition, the absence of a comprehensive legal definition of sexual violence worsens victims' access to protection. The implications of this research emphasize the need for legal policy reform and strengthening the capacity of LPSK to be able to carry out its protection mandate more inclusively and effectively.